ORGANIZATIONAL COMMUNICATION PATTERN OF GARDA DEPAN PT. ASELI DAGADU DJOKDJA IN INHERITING CORPORATE CULTURE - Brigita Luna Anggia Putri; Christina Rochayanti; Kartika Ayu Ardhanariswari (The Indonesian Journal of Communication Studies, 2019)
PT. Aseli Dagadu Djokdja is a Yogyakarta based alternative souvenir provider that has the slogan "Smart, Smile, Djokdja". Jogja's distinctive culture which is represented through various aspects makes PT. Aseli Dagadu Djokdja collaborates with the younger generation of future movers to work part-time as the leading service forces or known as Garda Depan. This study aims to determine the communication organization patterns formed on Garda Depan in passing on the corporate culture. The method used in this study is a qualitative research method by conducting in-depth interviews and observations as sources of research data, and using data triangulation techniques to test the validity of the data obtained. Garda Depan’s Program, which is one form of corporate social responsibility, lasts 8-12 months. With this personnel change cycle, the company implemented a training curriculum for candidates of Garda Depan to be able to pass on the various corporate cultures that exist in Dagadu. Through indoor training and internship at the recruitment stage, as well as 4an, sharing bulanan and internalan, there is an effort to inherit the culture from the company to the Garda Depan. Through organizational information theory, researchers found that communication patterns that occur are two-way by applying upward, downward, and horizontal communication. However, in its implementation there are obstacles in the form of language differences, seniority and the short duration of the internship. Althought that happens, it doesn’t reduce the process of developing relationships in Garda Depan who initially do not know each other to become a family with the whole of company.